The fate of art: Aesthetic alienation from Kant to Derrida and Adorno - Bernstein, J. (Cambridge Polity Press, 1992)
Aesthetic alienation may be described as the paradoxical relationship whereby art and truth have come to be divorced from one another while nonetheless remaining entwined. J.M. Bernstein not only funds the separation of and truth problematic, but also contends that we continue to experience sensuous and particular, thus comlicating and challenging the cultural self-understanding of modernity.Bernstein focuses on the work of four key philosophers--- Kant, Heidegger, Derrida, and Adorno--- and provides powerful new interpretations of their views. Bernstein shows how each of the three post-Kantian aesthetics (its concepts of judgement, genious, and the sublime) to construct a philosophical language that can criticize and displace the categorical assumption of modernity. He also examines in detail their responses to questions concerning the relations among art, philosophy, and politics in modern societies.